PENGARUH PROGRAM MATERNAL HEALTH LITERATION DALAM BUDAYA “BETAMUE” TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL - Ummi Latifah; Fitri Setianingsih; Nurlaila Agustikawati (Jurnal Ilmu Kebidanan, 2025)
Childbirth complications are one of the main causes of maternal death in Indonesia that occur due to high-risk pregnancies or deliveries and can threaten the lives of both the mother and the fetus, thus requiring appropriate midwifery care. Other factors that influence ANC visits include socio-cultural aspects, the level of anxiety of pregnant women, comfort, motivation, psychological factors, travel distance, support from health workers and family support. The purpose of this study was to determine the effectiveness of the Maternal Health Literacy Program in Betamue Culture in improving the knowledge and attitudes of pregnant women regarding ANC. This study is a Quasi-experimental study with a total sampling technique. The results showed that there was a significant difference in the average knowledge and attitudes of pregnant women before and after the implementation of the Maternal Health Literacy Program in Betamue culture. Which means that the Maternal Health Literacy Program in Betamue culture is effective in improving good knowledge and positive attitudes of pregnant women in ANC services.